Gender Issues in Digital Financial Literacy and Financial Behavior among Millennials - Febrianty, Febrianty; Yuliansyah, Yuliansyah; Hamzah, Ruth Samantha; Annisa, Mutiara Lusiana (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractThe study examines the effect of digital financial literacy on financial behavior which is proxied by spending and saving behavior. In particular, this study investigates the role of gender differences in the dependency relationship between digital financial literacy on financial behavior. The population was undergraduate students of the Faculty of Economics, Sriwijaya University, Indonesia. We employed the snowball sampling method and obtained 136 respondents as samples. Ordinary Least Square and Pairwise Comparisons were used to test the hypotheses. The results show that digital financial literacy has a positive and significant effect on spending behavior and saving behavior, respectively. Moreover, there is a difference between men and women in the effect of digital financial literacy on spending behavior. Nevertheless, it is found that there is no difference between men and women in the effect of digital financial literacy on saving behavior. Keywords:Digital Financial Literacy, Spending Behavior, Saving Behavior, Financial Behavior, Gender, Millennials